Adolescents and the Internet: Relationships and Social Competencies in the Physical and Digital World - Makrodimitri, Adamantia; Tragou, Elena (Homo Virtualis, 2023)
The excessive use of the Internet by adolescents nowadays is associated with the term “addiction” and seems to affect young people’s functioning in their daily activities, education, interpersonal relationships and mental health. Many studies have highlighted the association of excessive Internet use with lowered subjective well-being feeling, depressive symptoms, problematic behaviors, and a marked decrease in social integration. The aim of this research is to investigate adolescents’ long-term use of the Internet, the impact of this use on their mental health and how this use relates to their social skills and daily activities. Eight adolescents from a provincial seaside area of Attica, aged 14 to 18 years old, participated in the present study and responded to open-ended semi-structured interview questionnaire. The present research was based on the thematic method of qualitative analysis. From the analysis of the data six main thematic categories emerged, such as the Internet and its multitasking use, Companionship and Internet, Emotional effects and social anxiety, Exposure to danger and Getting mature through the internet use. This research shows that social media form a parallel universe for adolescents in which communication and socialization are its main benefits. Moreover, at the end of the article some suggestions/indications for further research on this issue are presented, as it seems that the influence of excessive internet use has consequences in many areas of adolescents’ lives.